Design and Implementation of a Smart, Interactive and Portable System for Monitoring of Human Vital Signs - Shahadi, Haider Ismael; Kadhim, Maha Khalid; Almeyali, Nawal Mousa; Hadi, Ali Thamir (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
Smart systems are characterized by their efficiency, high accuracy, and cost reduction. One of the important fields in which the smart system is used is health care, especially monitoring of human vital signs. In general, the conventional patient monitor is expensive, cannot be used for remote monitoring, and non-interactive. In many situations, it requires remote and portable monitoring for patients, such as in case of the area is outside the medical services, infected diseases (e.g., COVID-19, 20), and difficulties of a patient transferred. This paper proposes a smart, interactive, and portable monitor for vital human signs based on the internet of things (IoT). The proposed monitor is cheap and easy to use either directly by doctors and nurses or remotely by any person. The proposed system is designed using ESP32-microcontroller and vital-sign sensors. It measures three important vital signs, including heart rate, body temperature, and Electrocardiography (ECG), as well as the environment temperature of the patient. The measured signs can be monitored from anywhere in the world through a smartphone application in real-time. Furthermore, the doctor can send instructions and descriptions to the patients in real-time using the same phone application that is designed in this work.Smart systems are characterized by their efficiency, high accuracy, and cost reduction. One of the important fields in which the smart system is used is health care, especially monitoring of human vital signs. In general, the conventional patient monitor is expensive, cannot be used for remote monitoring, and non-interactive. In many situations, it requires remote and portable monitoring for patients, such as in case of the area is outside the medical services, infected diseases (e.g., COVID-19, 20), and difficulties of a patient transferred. This paper proposes a smart, interactive, and portable monitor for vital human signs based on the internet of things (IoT). The proposed monitor is cheap and easy to use either directly by doctors and nurses or remotely by any person. The proposed system is designed using ESP32-microcontroller and vital-sign sensors. It measures three important vital signs, including heart rate, body temperature, and Electrocardiography (ECG), as well as the environment temperature of the patient. The measured signs can be monitored from anywhere in the world through a smartphone application in real-time. Furthermore, the doctor can send instructions and descriptions to the patients in real-time using the same phone application that is designed in this work.